OPTIMIZATION OF ENGINE CONTROL UNIT PARAMETERS - Āboliņš, Dāvis; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
The aim of this work is to change car’s engine control unit’s parameters on-the-go, to achieve more power or more fuel economy. To reach named aim author in this work analyzed common method of switching car engine control unit’s parameters by using normal computer and considered utilizing single board computer and making a built-in system to switch easily desired driving style on-the-go.